Intimate partner violence indirectly dysregulates child diurnal adrenocortical functioning through positive parenting. Issue 1 (14th January 2020) - Hibel, Leah C.; Nuttall, Amy K.; Valentino, Kristin
Abstract: Data were drawn from an ongoing study of preschoolers ( N = 221). Mothers self‐reported experiences of intimate partner violence (IPV) and parenting practices, and collected three saliva samples (waking, midday, and bedtime) on themselves and their child on 2 consecutive days. Saliva samples were later assayed for cortisol. Bootstrapped mediation analyses revealed IPV to indirectly impact child diurnal cortisol through positive parenting. Specifically, greater exposure to IPV was associated with reduced positive parenting and subsequently heightened child waking cortisol levels. IPV did not indirectly impact child diurnal cortisol via autonomy supporting parenting or maternal diurnal cortisol. These findings suggest a possible pathway by which mother's experience of IPV indirectly influences child physiological regulation via maternal positive parenting.